Towards the development of a network library system for Philippine Public administration school libraries - Alfiler, Ana Grace P. (2008)
This study evaluates the technological capabilities of libraries offering Public administration in Metro Manila area to initiate and sustain a library network. It aims to bring together the local collections in the field of public administration, to simplify searching through available resources. It focused on the libraries of member schools of the Association of Schools of Public Administration in the Philippines (ASPAP). Fourteen of the seventeen school members located in Metro Manila agreed to participate in the study. A four-page questionnaire was distributed to the head/chief librarians of the participating libraries. The questionnaire focused on the library's level of digitalization, availability of computer equipment, personnel, level of professional training and size and nature of the collection in the field of public administration. Follow-up interviews were done to probe certain responses. The study revealed that among librarians of ASPAP schools in Metro Manila only five librarians were aware of the association and its activities.